2011
DOI: 10.1002/bdrc.20210
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity screening in zebrafish

Abstract: Given the ever-increasing toxic exposure ubiquitously present in our environment as well as emerging evidence that these exposures are hazardous to human health, the current rodent-based regulations are proving inadequate. In the process of overhauling risk assessment methodology, a nonrodent test organism, the zebrafish, is emerging as tractable for medium- and high-throughput assessments, which may help to accelerate the restructuring of standards. Zebrafish have high developmental similarity to mammals in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 241 publications
(263 reference statements)
3
101
0
3
Order By: Relevance
“…The notochord initiates angiogenic sprouting from these primary vessels by secreting sonic hedgehog (SHH), which upregulates vascular endothelial growth factor A (VEGFA) expression and secretion in adjacent myotomes. Secreted VEGFA is present in free (VEGFA121) and extracellular-matrix (ECM)-bound forms (VEGFA165 Arsenic (As), an environmental toxin, inhibits angiogenic ISV sprouting in zebrafish, resulting in shorter length, irregularly oriented, or entirely missing ISVs [2,7]. Our analyses of ISV growth dynamics showed that these changes result from decreased directed migration speed and perturbation of directional path-finding [7].…”
mentioning
confidence: 93%
“…The notochord initiates angiogenic sprouting from these primary vessels by secreting sonic hedgehog (SHH), which upregulates vascular endothelial growth factor A (VEGFA) expression and secretion in adjacent myotomes. Secreted VEGFA is present in free (VEGFA121) and extracellular-matrix (ECM)-bound forms (VEGFA165 Arsenic (As), an environmental toxin, inhibits angiogenic ISV sprouting in zebrafish, resulting in shorter length, irregularly oriented, or entirely missing ISVs [2,7]. Our analyses of ISV growth dynamics showed that these changes result from decreased directed migration speed and perturbation of directional path-finding [7].…”
mentioning
confidence: 93%
“…Zebrafish has become an important model for biological and pharmacological research [1][2][3] . Tracking of movement and spatial distribution patterns of individual zebrafish and of shoals of zebrafish is invaluable.…”
Section: Introductionmentioning
confidence: 99%
“…It has many advantages, including small size, rapid and ex-utero embryonic development, and high breeding rates. Moreover, the embryo is optically transparent, making it amenable to observation of complex developmental events under the microscope 9 . It is an ideal animal model for the study of migration and differentiation of cranial neural crest cells.…”
Section: Introductionmentioning
confidence: 99%